Improving Relationships and Student Outcomes Through Restorative Practices. (September 2022) - Forsberg, Malinda L.; Leko, Melinda M.
Students who exhibit externalizing behaviors may impede learning in the classroom and lead to cycles of negative teacher–student interactions. Positive relationships among students, peers, and educators serve as a protective factor against childhood adversity and are a predictor of academic, social, and behavioral outcomes. By incorporating restorative practices into their daily routine, educators and school leaders can strengthen relationships and promote safety while ensuring students are learning prosocial skills needed for future success.